A prospective cohort study of quality of life and ischemic heart disease. Issue 1 (February 2014) - Mikkelsen, Stine Schou; Mortensen, Erik Lykke; Flensborg-Madsen, Trine
Aims : To examine the role of self-rated quality of life, as a whole, on the risk of developing ischemic heart disease. Methods : Information on self-rated quality of life and covariates was obtained from 4497 people from the Copenhagen Perinatal Cohort. The study population, consisting of both men and women aged 31–33 years at baseline, was followed for registration of ischemic heart disease in national registers. Two different follow-up periods were examined. Results : Using a follow-up of 13 years, the basis-adjusted hazard ratio among women who rated their quality of life as poor was 2.93 (95% CI: 1.09–7.86), compared with women who rated their quality of life as very good. The hazard ratio of women who rated their quality of life as good, compared to very good, was 2.99 (95% CI: 1.22–7.29). When analyzing 16 years of follow-up, estimates among women were lower and some of the hazard ratios were insignificant. All hazard ratios among men were below two and none were statistically significant. Conclusions : Among women, the risk for ischemic heart disease was two to four times greater for those who rated their quality of life as poor or good, than for women with the most positive rating. For men, the association was not statistically significant.